2008
DOI: 10.1002/bip.21115
|View full text |Cite
|
Sign up to set email alerts
|

The third and fourth transmembrane domains of Slc11a1: Comparison of their structures and positioning in phospholipid model membranes

Abstract: Interactions of two peptides TM3 and TM4, corresponding to the third and fourth transmembrane domains of a divalent metal-ion transporter Slc11a1, respectively, with phospholipid model membranes, including zwitterionic dimyristoylphosphatidylcholine (DMPC) and anionic dimyristoylphosphatidylglycerol (DMPG), are studied in a wide range of peptide-to-lipid (P:L) ratios, and the secondary structures and positioning of the peptides in the lipid bilayers are analyzed, using differential scanning calorimetry (DSC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The spectra were scanned three times for each sample and averaged, and the blank was subtracted from all spectra. Final spectra were smoothed using a FFT filter, and the intensity was expressed as mean residue ellipticity . Secondary structure analysis was performed by CDPro software package .…”
Section: Methodsmentioning
confidence: 99%
“…The spectra were scanned three times for each sample and averaged, and the blank was subtracted from all spectra. Final spectra were smoothed using a FFT filter, and the intensity was expressed as mean residue ellipticity . Secondary structure analysis was performed by CDPro software package .…”
Section: Methodsmentioning
confidence: 99%
“…The insertion position of TMS4 in the model membrane is affected less by pH than the position of TMS3. 38 These experiments have also demonstrated the importance of D192 located in TMS4 of Nramp2 for manganese binding. 37 Mutation at this position in Nramp2 (D192A) was previously shown to attenuate the uptake of cobalt and iron in cells.…”
mentioning
confidence: 89%
“…31 Moreover, some unusual transport properties of Nramp proteins described previously can be interpreted in terms of channel-like mechanism. 15 So far, TMS3 and TMS4 of eukaryotic DMT1 (Nramp2) [32][33][34][35] and of eukaryotic Nramp1 [36][37][38] have been studied exclusively from the structural point of view. It has been shown that TMS4 of Nramp1 is buried more deeply in model lipid bilayers than TMS3.…”
mentioning
confidence: 99%
“…In our previous work, we have studied the structures and topologies of the peptides corresponding to the TMD1 and TMD6 of Slc11a2/DMT1 , TMD3 and TMD4 of Slc11a1 and some peptides from specific site mutations of these transmembrane domains in both organic solvents and detergent micelles using CD and NMR methods. We also studied the secondary structures and topologies of TMD1‐TMD5 of Slc11a1 in lipid membranes by CD and attenuated total reflectance (ATR) FTIR techniques.…”
Section: Introductionmentioning
confidence: 99%